2023
DOI: 10.3390/pharmaceutics15020681
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Chitosan-Based Nanomedicine for Its Ocular Application in Glaucoma

Abstract: Glaucoma is a degenerative, chronic ocular disease that causes irreversible vision loss. The major symptom of glaucoma is high intraocular pressure, which happens when the flow of aqueous humor between the front and back of the eye is blocked. Glaucoma therapy is challenging because of the low bioavailability of drugs from conventional ocular drug delivery systems such as eye drops, ointments, and gels. The low bioavailability of antiglaucoma agents could be due to the precorneal and corneal barriers as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Studies highlight the effectiveness of chitosan nanoparticles in enhancing drug delivery to the eye, addressing challenges such as low bioavailability and limited drug retention times associated with conventional drug delivery systems. Various studies have indicated that chitosan nanoparticles can improve the delivery and efficacy of antiglaucoma agents by overcoming barriers such as poor residence time and low corneal permeability, which are common limitations of traditional ocular pharmaceutical products [ 148 ]. Additionally, the mucoadhesive properties of chitosan also contribute to its potential applications, aiding in sustained drug release and enhanced therapeutic performance for glaucoma management [ 149 ].…”
Section: Biopolymeric Drugs Delivery Systemsmentioning
confidence: 99%
“…Studies highlight the effectiveness of chitosan nanoparticles in enhancing drug delivery to the eye, addressing challenges such as low bioavailability and limited drug retention times associated with conventional drug delivery systems. Various studies have indicated that chitosan nanoparticles can improve the delivery and efficacy of antiglaucoma agents by overcoming barriers such as poor residence time and low corneal permeability, which are common limitations of traditional ocular pharmaceutical products [ 148 ]. Additionally, the mucoadhesive properties of chitosan also contribute to its potential applications, aiding in sustained drug release and enhanced therapeutic performance for glaucoma management [ 149 ].…”
Section: Biopolymeric Drugs Delivery Systemsmentioning
confidence: 99%
“…Hence, glaucoma diagnosis and monitoring are very essential, and can be achieved by measuring the IOP [ 49 ]. In affected individuals, both retinal ganglion cells and retinal axons become damaged due to high levels of IOP and oxidative stress [ 50 ].…”
Section: Ocular Diseasesmentioning
confidence: 99%
“…Chitosan, a cationic hydrogel polymer, is widely used among these polymers. This is due to the fact that chitosan has great biocompatibility and includes an amino group that may be readily protonated [ 88 ]. Recently, Nguyen et al prepared pilocarpine-loaded ceria nanogel (Ce NC) coated with chitosan hydrogels for ocular application [ 89 ].…”
Section: Recent Progress and Challenges In Overcoming Biological Barr...mentioning
confidence: 99%